Developing Physical Activity-Based Ular Tangga Rahasia Learning Media to Enhance Early Childhood Gross Motor Skills - Wara Rina Wahyuni; Hadiqotul Luluk; Zakirman; Erie Siti Syarah (Jurnal Educative: Journal of Educational Studies, 2025)
This study aimed to develop a physical activity-based Ular Tangga Rahasia media to improve early childhood gross motor skills. This research employed a Research and Development (R&D) method using the 4D development model consisting of define, design, develop, and disseminate stages. The research subjects consisted of 30 children aged 5–6 years. Data collection instruments included expert validation sheets, teacher response questionnaires, observation sheets, and children's gross motor skill tests. Data were analyzed using descriptive quantitative analysis and paired sample t-test. The results showed that the developed media had a very high level of validity, with an average score of 90% from media experts, 92% from material experts, and 93.5% from language experts. The practicality test results obtained an average score of 93% categorized as very practical. In the effectiveness test, the average gross motor skill score increased from 61.6 in the pretest to 86.3 in the posttest, with an improvement of 24.7 points. The paired sample t-test results showed a significance value of 0.000 (<0.05), indicating that the media effectively improves early childhood gross motor skills. Improvements were observed in balance, coordination, agility, strength, and locomotor movement indicators. Therefore, the physical activity-based Ular Tangga Rahasia media is considered valid, practical, and effective and can be used as an innovative learning media to improve early childhood gross motor skills.